ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KOMPETENSI YANG BERDAMPAK PADA KINERJA PEGAWAI BALAI PENGELOLA TRANSPORTASI DARAT (Studi Kasus di Balai Pengelola Transportasi Darat Wilayah VII Provinsi Sumatera Selatan dan Provinsi Bangka Belitung) - Amri Amri (Jurnal Ilmiah Hospitality, 2023)
This research is a quantitative research with a survey approach to analyze the effect of mastery of information technology, work motivation and job description on competence and the effect of competence on performance. The number of samples was 221 employees of the Land Transportation Management Center Region VII, South Sumatra Province and Bangka Belitung Province. Testing the quality of the data used is the test of validity, reliability, normality, multicollinearity, linearity heteroscedasticity, and analysis of the coefficient of determination. The data analysis model uses path analysis with F test and t test. The results showed that the variables of Mastery of information technology (X1), Work Motivation (X2), and Job Description (X3) simultaneously had a significant effect on the competence of employees at the Land Transportation Management Center Region VII, South Sumatra Province and Bangka Belitung Province (Y) by calculating F test obtained Fcount (43.786) > Ftable (2.648), and a significance value of 0.000 <0.05. From the t-test calculation, it is known that partially the Mastery of information technology (X1), Work Motivation (X2) and Job Description (X3) variables have a significant influence on Competence (Y) with the t-count calculation of the Training variable (X1) of tcount (2.148) > ttable (1,971), Work Motivation variable (X2) is tcount (4,860) > ttable (1,971), Job Description variable (X3) is tcount (5,319) > ttable (1,971). From the calculation of the t test, it is known that partially the Competence variable (Y) has a significant influence on the Performance variable (Z) of tcount (2.518) > ttable (1.971).